EFEKTIVITAS REGULASI PENGELOLAAN ASET NEGARA DALAM MENINGKATKAN PENDAPATAN NEGARA - Clodya, Ferika; Nursyidah; Mazura, Desi; Rahim, Rafidah (Triwikrama: Jurnal Ilmu Sosial, 2025)
State asset management plays a very important role in increasing state revenue, which in turn can be used to finance development and improve public welfare. In recent years, Indonesia has developed various regulations governing state asset management, including more targeted and efficient management policies and strategies. However, the effectiveness of these regulations still needs to be evaluated, because challenges in state asset management such as lack of transparency, lack of coordination between agencies, and suboptimal utilization of state assets still occur. This article aims to analyze the effectiveness of state asset management regulations in increasing state revenue and identify obstacles and challenges in their implementation. With a qualitative approach involving literature review and policy analysis, the results of this study are expected to contribute to improving state asset management policies and regulations in Indonesia. The findings in this article indicate that although state asset management regulations are quite adequate, there are several obstacles that affect their effectiveness in increasing state revenue, including limited human resources and a weak monitoring system.